THE FACTORS INFLUENCE TAXPAYER'S INTENTIONS TO DO THEIR OBLIGATION - Icuk Rangga Bawono; Rasyid Mustofa; Medika Danang Indanto (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2020)
This study has a purpose to examines the level of compliance of individual taxpayer who undertakes the business activity and independent personal service by using several independent variables such as taxpayer awareness, tax authorities service, taxpayer knowledge and tax penalty. The purpose of this study was to analyze taxpayer awareness, tax authorities service, taxpayer knowledge, and tax penalty toward individual taxpayer compliance who undertakes the business activity and independent personal service.The population of this study is individual taxpayer who undertakes the business activity and independent personal service. This study use purposive sampling tehnique to collect samples. The number of sample is 99 taxpayers. Primary data collection method used is a survey method using questionnaires. Collected data on this study precessed by multiple regression analysis. Based on the results of analysis undertaken concluded that taxpayer awareness, tax authorities service, taxpayer knowledge, and tax penalty have a positive and significant effect toward taxpayer compliance.